Effect of temperature on the hydrolysis of levan treated with compressed hot water fluids - TOKSOY ÖNER, EBRU (WILEY, 2020)
The hydrolysis of levan using compressed hot water for the production of functional fructooligosaccharides (FOSs) was investigated. Levans from Erwinia herbicola (EH) and Halomonas smyrnensis (HS) were characterized using scanning electron microscopy and light scattering techniques, and hydrolyzed using compressed hot water at four temperatures (120, 140, 160, and 180 degrees C). The hydrolysates were analyzed using high-performance liquid chromatography and electrospray ionization-mass spectrometry. Levan HS showed a crystalline morphology, whereas levan EH showed an aggregated structure. Both levans had molar masses on the order of 10(6) g/mol, but levan EH had a smaller radius of gyration, hydrodynamic radius, and intrinsic viscosity. Levan EH hydrolyzed into FOSs at approximately 120 degrees C, whereas levan HS required a temperature of at least 160 degrees C, possibly because of differences in the degree of branching of the two levans. Both samples were degraded to fructose when treated at 180 degrees C.
Keywords: compressed hydrolysate; fructooligosaccharides; levan; light scattering; PHYSICOCHEMICAL PROPERTIES; FRUCTAN; POLYSACCHARIDE; CONFORMATION; INULIN; FIELD